Sistem Komputerisasi Absensi Pegawai Pt Mitra Informatika Dengan Menggunakan Fasilitas Barcode Dan Penerimaan Gaji Insentif Bagi Pegawai Berdasarkan Absensi - Septania Windy Maharani; Muryan Awaludin (Fakultas Ilmu Komputer & Desain, 2024)
The development of science and technology (science and technology) is currently experiencing very rapid progress, especially in the computer world. The application of Information Technology (IT) has now spread almost in all fields. The use of increasingly advanced technological tools today will greatly help entrepreneurs to develop their businesses. With proper data processing, accurate and fast information will be obtained to make the company's performance more efficient. Computers with adequate hardware and software will be very helpful in carrying out company activities. Software that is easily understood by users will greatly assist in data processing which will then become the information needed to improve work efficiency and assist in making important decisions in the company. Staffing Division of PT. Mitra Informatics is a part whose performance is quite heavy, because this section regulates employee discipline regarding attendance which is very influential on the progress of the company. In the personnel division of PT. Mitra Informatics, there is a need for an information system that helps the data processing operational activities needed, so that with a computerized employee attendance system will be very influential for the smooth performance of employees which ultimately will also be very influential for the progress of the company.